ЎЗ ЮРТИДАН ПАНОҲ ИЗЛАГАН ШОҲ ВА ШОИР - Амирқулова, З.М. (SCIENCE and SOCIETY, 2020)
The article deals with the work "Panah" by the famous writer Khayriddin Sultanov, where the features of the image of Babur are described in the light of historical events.